Cytopathologic, Histopathologic, and Immunohistochemical Features of Intrahepatic Clear Cell Bile Duct Adenoma: A Case Report and Review of the Literature - William W. Wu; Mai Gu; Di Lu (Case Reports in Pathology)
Intrahepatic clear cell bile duct adenoma is extremely rare, with only 3 previous cases reported in the literature. The cause of cytoplasmic clearing in clear cell bile duct adenoma has not been previously investigated. Distinguishing clear cell bile duct adenoma from other clear cell tumors, particularly clear cell cholangiocarcinoma, can be challenging. Previous studies have shown loss of CD10 expression and focal CD56 expression in cholangiocarcinoma. Expressions of CD10 and CD56 have not been previously studied in clear cell bile duct adenoma. A 37-year-old morbidly obese woman was diagnosed with a 2.8 cm intrahepatic clear cell bile duct adenoma following segmental hepatic resection. Histochemical analysis of the tumor suggested the cause of cytoplasmic clearing in the neoplastic cells to be mucin and not glycogen or lipid. On immunohistochemical staining, the neoplastic cells demonstrated staining for CK7, CA 19-9, polyclonal CEA, CD10 (apical), CD56 (focal), and vimentin. Ki-67 highlighted less than 2% of tumor cell nuclei. This is the first report to study the etiology of cell clearing in clear cell bile duct adenoma. Expression of CD10 in clear cell bile duct adenoma may help distinguish clear cell bile duct adenoma from clear cell cholangiocarcinoma.